Recent State and Mechanisms of Invasions of Exotic Decapods in Ukrainian Rivers - Son, M.O.; Novitsky, R.A.; Dyadichko, V.G. (Вестник зоологии, 2013)
Lower reaches of largest Ukrainian rivers are zones of migrations for exotic euryhaline decapods. During 2000s new records of invasions of three euryhaline exotic decapods, Rhithropanopeus harrisii (Gould, 1841), Eriocheir sinensis Milne-Edwards, 1853 and Macrobrachium nipponense (De Haan, 1849), were made in the channels of Ukrainian rivers. Chinese mitten crab, E. sinensis, spread in the Danube Delta and reservoirs of the Dnieper River; Rh. harrisii — in the channels of the Danube, Dnieper, Southern Bug and small river Gruzskij Yelanchik in the Azov Sea Basin; M. nipponense that was introduced in the Kuchurgan Liman (cooler reservoir of the Moldavian Hydro-power Station) — in the Dniester Delta. The migration zone of the established population can cover significant part of river watershed; it is necessary to take this fact into account at an estimation of biological invasion risk. Main problem in the investigation of exotic decapods in Ukrainian waters is absence of specialized methods used in the standard ecological monitoring. Among euryhaline exotic decapods, only Rh. harrisii is sometimes sampled with the equipment used in the monitoring of macrozoobenthos. A few records of these species at the large extent of their supposed ways of migration are the result of gaps in the study of their distribution in Ukrainian inland waters. Realistic attitude toward this fact is very important for the estimation of invasions in the inland waters of this region.